Antioxidants Activity of Self-Nanoemulsifying Drug Delivery System on Dayak Onions Extract (Eleutherine palmifolia) using DPPH (2,2 difenil-1- picrylhydrazyl) Method - Rahmi Annisa; Tanaya Jati Dharma; Roihatul Mutiah; Sitti Nurjannah (Journal of Tropical Pharmacy and Chemistry, 2021)
Dayak onions (Eleutherine palmifolia L. Merr) is one plant that has been proven to have benefits as an antioxidant. The Dayak extract is formulated in the self nano emulsifying drug delivery system (SNEDDS) because the extract has low water solubility. The aims this study to develop the SNEDDS formulation system by testing its antioxidant activity. We determined whether there was an increase in antioxidant activity when formulated in the form of SNEDDS or not. The results were then compared with a solution of Dayak onions extract without using SNEDDS. The obtained formula was the optimal result that has been done before using the D-optimal mixture design method. The results of the components consisted of 50 mg of Dayak extract, 10 % caprylic triglyceride as oil, 1% tween 80, and 6,60 % transcutol as a combination surfactant and 12,40 % propylene glycol as co-surfactant. Antioxidant activity testing was carried out using the DPPH (1,1-Diphenyl-2-picrylhydrazyl) method. The antioxidant test using the DPPH method was done with two samples, namely the extract solution and Dayak onion extract SNEDDS. We elaborated the research by using UV-VIS spectrophotometer. Each sample was made into five concentrations, namely 30 ppm, 60 ppm, 90 ppm, 120 ppm, and 150 ppm, and carried out three times replications. The results showed that the IC50 value in the Dayak onion extract solution was 227,19 ppm (very low), while for the SNEDDS solution for the Dayak onion extract the IC50 value obtained was 38,97 ppm (very strong). The analysis was carried out next using an independent T-Test to obtain the results. There was no significant difference between the extract solution and the SNEDDS solution of Dayak onion extract.